21st International Conference on Offshore Mechanics and Arctic Engineering, Volume 3 2002
DOI: 10.1115/omae2002-28611
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Models of Uncertainties in Fatigue and Fracture Reliability Analysis

Abstract: Probabilistic methods enable the modelling of the uncertainties associated with the integrity assessment of structures containing defects to be taken into account. This paper presents a critical review of recent developments in the probabilistic modelling of the uncertainties associated with fatigue and fracture reliability assessment. A number of probabilistic models for the principal parameters in the S-N curve, fatigue crack growth functions and fracture analysis are presented and discussed with particular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In engineering critical assessment (ECA), when reliable data over the whole range of possible values are not available, it is common to treat one or all of these parameters deterministically by assuming (an) upper/lower bound value(s). In reliability analyses, however, accurate and realistic defect size distributions is a vital input [32]. The choice of distribution type depends on two factors: 1. the nature of the physical phenomena modelled and 2: the goodness of fit of the data to distribution.…”
Section: Defect Sizementioning
confidence: 99%
“…In engineering critical assessment (ECA), when reliable data over the whole range of possible values are not available, it is common to treat one or all of these parameters deterministically by assuming (an) upper/lower bound value(s). In reliability analyses, however, accurate and realistic defect size distributions is a vital input [32]. The choice of distribution type depends on two factors: 1. the nature of the physical phenomena modelled and 2: the goodness of fit of the data to distribution.…”
Section: Defect Sizementioning
confidence: 99%
“…Zhao et al [11] found that the CoV varies from case to case, and recommends a log normal distribution with mean 𝜇 = 1 and CoV = 0.45 based on averaging results from a number of tests/models, as shown in…”
Section: Uncertainty Of Miner's Rule δmentioning
confidence: 99%
“…Letting D = Ap, the basic damage expression of Eq. (10) can be expressed in terms of the time to failure T = (12) Log (Stress intensity factor range, K)…”
Section: =mentioning
confidence: 99%
“…Risk assessment is essential to regulate the design so that the resulting structure is safe, serviceable, and economical, ensuring satisfactory performance during its design life period. As evidenced from similar applications in offshore structures [5][6][7][8] and other steel structures [9][10][11][12], one possible avenue for meeting these objectives is the implementation of the fracture mechanics approach, in light of the load and response uncertainties, probabilistic modeling, and reliability analysis. The work described in this paper is aimed at the development of a probabilistic methodology for the assessment of marine structures using the bilinear S-N curve and fracture mechanics approaches.…”
Section: Introductionmentioning
confidence: 99%